USING SCORECARD TO ANALYSE RISK FACTORS OF STROKE IN WEST SUMATERA INDOENSIA - Srywahyuni, Ade; Amelia, Dona; Merianti, Liza; Wulandari, Senci Napeli (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Stroke is one of the most frightening diseases because it may cause major deaths in Indonesia. Recently, it has caused the death for about 21.1% of all ages. The World Health Organization (WHO) predicts that deaths caused by stroke will increase?every 45 seconds a person has a stroke, and?every 4 seconds there is a death caused by stroke. At this time, there is a shift in the phenomenon; stroke does not only suffer the elderly patients, but it has now attacked the productive age or young age also.The purpose of this study was to identify the proporsion of risk of stroke in productive age of Bukittinggi population based on Risk Scorecard.Method: The study used a survey analytic study design with approach cross-sectional. This was a population ? based survey of adult households in Indonesia is about 24130 individu. The sample of this study was 322 respondents where they were taken by using simple random Sampling technique. The subjects were visited at their homes for recruitment and data collection. In each household, one or more eligible subject above the age of 18. The subject were exclude if they were mentally unable to answer the questionnaire, were not a resident in Bukittinggi, or directly declined to participate. Result: Individuals at high risk of stroke are 20.5%, 22.4% in case of caution, and 57.1% respondents at low risk of stroke. The results of this study represent the risk of stroke with the highest frequency of distribution was in low risk respondents. It was then followed by caution respondents. The lowest frequency was scored for high risk respondents.Conclusion: The proportion of stroke of risk found in the productive age population of Bukittinggi that were based on risk scorecard.